Os filhos de ninguém : a garantia do direito a convivência familiar e comunitária no serviço de acolhimento para crianças no município de Cuiabá - Silvério, Samanta Gomes Rosa (2017)
The research developed aimed to analyze the access of children to the right to family and community life, in the light of the National Plan for the Promotion, Protection and Defense of the Right to Family and Community Life of children and adolescents - PNCFC, in institutional care units. from the municipality of Cuiabá. The empirical field of the research is constituted by the institutions: Superintendência de Acolhimento Social – Lar da Criança and the three Nursing Homes: Casa da Criança Cuiabana I, Casa da Criança Cuiabana II and Casa da Criança Cuiabana III, which were the existing units in the period. where the research was conducted (December / 2016). The research is of the documentary type of qualitative nature. In order to achieve the established proposals and to deepen the knowledge inherent to the guiding categories of the process of institutionalization of children in the country as a public policy guaranteeing rights, we conducted a historical context to shed light on the research developed. It then approaches the historicity of the childcare institutions in Cuiabá, placing them in the context of the childcare policy that in Brazil has new contours since the 1988 Federal Constitution, the 1990 ECA and more precisely the PNCFC, and all of them. the subsequent national directives, as a result of the reorganization required by national policy, the consequences of which are yet to be verified, especially as regards the consonance with the guidelines established for the whole country regarding social protection. We concluded that for many years, the institutional care unit - Lar da Criança - was considered a “model institution” propagated successively by state governments, because it had a large and complete team of professionals, which was, in fact, a big mistake. and materialized the history of Mato Grosso, which does not differ from the history of the country when we talk about total institutions, because it is very harmful to child development in many aspects, as we will see in this paper. Regarding the three existing Nursing Homes in Cuiabá, and despite the short time of existence for more definitive conclusions, analyzing the data of the Individual Reception Plan - PIA and reception reports, we can infer that the right to family life is reached and can be achieved. considered respected, since the three houses maintained family life when allowed in court, if they did not seek measures to ensure that the child had this right consolidated. On the other hand, although welcoming is understood as a viable and appropriate measure for the materialization of social guarantees, rights and protection for children and adolescents away from their family life, it has the historical limitation of segregating these subjects.